2021
DOI: 10.3390/ijms22052749
|View full text |Cite
|
Sign up to set email alerts
|

Auxin and Root Gravitropism: Addressing Basic Cellular Processes by Exploiting a Defined Growth Response

Abstract: Root architecture and growth are decisive for crop performance and yield, and thus a highly topical research field in plant sciences. The root system of the model plant Arabidopsis thaliana is the ideal system to obtain insights into fundamental key parameters and molecular players involved in underlying regulatory circuits of root growth, particularly in responses to environmental stimuli. Root gravitropism, directional growth along the gravity, in particular represents a highly sensitive readout, suitable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 161 publications
(219 reference statements)
0
28
0
Order By: Relevance
“…Auxin forms gradients and concentration maxima in tissues and organs to stimulate diverse biological processes including gravitropism [ 5 , 6 ], organ initiation [ 7 ], leaf venation [ 8 ], apical dominance [ 9 ], embryo axis formation [ 10 ], root architecture [ 11 ], leaf vascular development [ 12 ], tropisms [ 13 , 14 ], fruit ripening [ 15 ], phototropism [ 16 ], phyllotactic patterning [ 17 ], lateral root emergence [ 18 ], root hair growth [ 19 ], apical hook development and root patterning [ 20 ], and sporophyte and male gametophyte development [ 21 , 22 ]. Several researchers have demonstrated that metabolic changes and transport of auxin play a key role in tissue differentiation, embryogenesis, organogenesis, differential growth, and tropic responses [ 2 , 3 , 4 , 23 , 24 , 25 , 26 ]. Auxin is synthesized in various plant tissues by several different pathways [ 27 , 28 ] and subjected to long- and short-range transport mediated by influx and efflux auxin transporters [ 25 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Auxin forms gradients and concentration maxima in tissues and organs to stimulate diverse biological processes including gravitropism [ 5 , 6 ], organ initiation [ 7 ], leaf venation [ 8 ], apical dominance [ 9 ], embryo axis formation [ 10 ], root architecture [ 11 ], leaf vascular development [ 12 ], tropisms [ 13 , 14 ], fruit ripening [ 15 ], phototropism [ 16 ], phyllotactic patterning [ 17 ], lateral root emergence [ 18 ], root hair growth [ 19 ], apical hook development and root patterning [ 20 ], and sporophyte and male gametophyte development [ 21 , 22 ]. Several researchers have demonstrated that metabolic changes and transport of auxin play a key role in tissue differentiation, embryogenesis, organogenesis, differential growth, and tropic responses [ 2 , 3 , 4 , 23 , 24 , 25 , 26 ]. Auxin is synthesized in various plant tissues by several different pathways [ 27 , 28 ] and subjected to long- and short-range transport mediated by influx and efflux auxin transporters [ 25 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Redistribution of auxin plays an important role in plant gravitropism [ 1 , 11 , 57 , 58 , 59 , 60 , 61 ]. We followed the establishment of the auxin gradient by the auxin induced DR5::GFP construct [ 59 ] in vertically placed and rotated roots with and without PQ treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It is well accepted that the bending of the root towards the gravity vector is due to the asymmetry in the auxin distribution between the lower and upper tissues of the horizontally oriented root tip [ 1 , 57 , 58 , 59 , 61 , 64 ]. The asymmetry in auxin distribution is due to the gravity-induced differential regulation of the turnover of PM-bound auxin transporter proteins (including AUX1, PIN3, and PIN2) at the two sides of the root.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations